MODIFIKASI METODE DEKOMPOSISI ADOMIAN UNTUK MENYELESAIKAN PERSAMAAN GELOMBANG NONLINEAR - Widiya Fitrina Sari; Leli Deswita; Endang Lily (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This article discusses the modification of Adomian decomposition method to solve anonlinear wave equation. Some numerical examples are used to show the effectivenessof the method. The numerical result show that the solution obtained through themodification of Adomian decomposition method is better than the solutions obtainedusing Adomian decomposition method.